Impact of COVID-19 on economic and working conditions in Italy. Data from PASSI and PASSI d'Argento. (20th October 2021) - Possenti, V; Minardi, V; Contoli, B; Lana, S; Scardetta, P; Masocco, M
Abstract: Background: Having affected multiple life aspects globally, the COVID-19 pandemic will generate long-term consequences on productive sector and economy. The two Italian population-based surveillance systems PASSI (18-69yy) and PASSI d'Argento (65+) have annexed a COVID-module to the standard questionnaires' sections to investigate also changes of economic and working conditions related to the COVID-19 crisis. Methods: We analysed data on a sample of 2, 613 PASSI and 2, 288 PASSI d'Argento interviews, collected between August and December 2020. Results: Among adults, 34% refers a worsening of their financial resources because of the COVID-19 crisis: above all if socially deprived people, with many difficulties (52%) or with a low educational level (41%). Despite keeping up working, 31% of employed people worked less due to the COVID crisis, with a lower wage; 5.5% lost the job and a certain number had to give it up. The worsening of economic resources correlates to changes in working conditions due to the pandemic crisis, but the latter did not fully determine the former. Economic losses are more frequent among people in search of employment (52% vs 35% of occupied or 28% of inactive), those who lost their job (76%) or, despite keeping up working, earn less (66%), but interest also individuals who have not undergone changes per the working condition and volume (19%). The association between worsened economic resources and social disadvantage (low education and economic difficulties) is significant, even adjusting for job or wage loss. Even among older persons, a lower but non-negligible quota (16%) declares economic worsening due to the pandemic-related crisis. The percentage triples (29%) on difficulty making ends meet. Conclusions: Since the analysis of preliminary findings, it emerges how the impact of this crisis is and will not be the same to all, but will emphasize inequalities, at the expense of the most vulnerable individuals, at any age. Key messages: In Italy, the COVID-19 pandemic has affected the main social determinants of people health because it has worsened economic and working conditions. This crisis is emphasizing health inequalities, at the expense of the most vulnerable individuals, at any age.